Seismic Response of Vertical Irregular Structures in Setback and Stepped Buildings - Bhatta, Surendra; Sharma, Latip Kumar; Niure, Bharat; Niraula, Sudhir (Journal of Engineering Technology and Planning, 2021)
Vertical irregular buildings are frequently constructed across the globe for functional as well as aesthetic purpose. However post-earthquake reconnaissance survey reports revealed high seismic vulnerability of the building with vertical irregularities. Consequently it is very important to explore the reason behind the high seismic vulnerability and the poor performance of irregular structures during the earthquake. A humble effort is under taken considering several case studies comprising different configuration of vertical irregular structures, so as to comprehend the seismic behavior of vertical irregular structure using response spectrum and pushover analysis has been attempted in finite element software ETABS 16.2.1 version. The results of the analysis indicate the irregular structures have ample chance of higher stress concentration as well as higher displacement demand at the vicinity of irregularity. Member strength enhancement at the vicinity of vertical irregularity may improve the overall seismic performance of the building. Also, this research checks the adequacy of fundamental mode properties for the quantification of vertical irregularity. Furthermore, pushover analysis has been done to observe the hinge formation pattern and also the plastic hinge rotation for observing the performance level of building.